STRATEGI PERTUMBUHAN BERKELANJUTAN BAGI KOPERASI SIMPAN PINJAM MARENDENG DI ERA DIGITAL - Leorensius Pelix; Mellda Ati Pallangan; Bernadeth Tongli (Jurnal Riset Akuntansi, 2025)
Savings and Loan Cooperatives (KSP) play a role in increasing financial inclusion, but face challenges in the digital era due to competition with fintech and digital banking. This study analyzes sustainable growth strategies for KSP using qualitative literature study methods. The results of the study indicate that digitalization can improve operational efficiency, expand financial access, and increase KSP competitiveness. The main strategies that can be implemented include service digitalization, strengthening governance, increasing digital literacy, and collaboration with fintech. The main challenges faced are limited technological infrastructure and regulatory complexity. Therefore, KSP needs to adopt an adaptive strategy to remain competitive and sustainable amidst digital change. This study contributes to providing strategic insights for KSP managers and becomes a reference for regulators in supporting cooperative digitalization.